A multilingual background for telecollaboration: Practices and policies in European higher education. Issue 2 (October 2019) - Arnó-Macià, Elisabet; Vandepitte, Sonia; Minacori, Patricia; Musacchio, Maria Teresa; Hanson, Joleen; Maylath, Bruce
Abstract : The Trans-Atlantic and Pacific Project (TAPP) is a telecollaboration network linking European university classes with classes in the US and beyond for nearly 20 years. Such collaborations have enabled students to participate in realistic projects, fostering transversal and language skills – including English as a lingua franca – which are highlighted in university policies at European, country/region and institutional levels. In turn, telecollaboration can support Internationalisation at Home, along with virtual mobility objectives, increasingly prominent in European higher education. Considering the grassroots nature of TAPP, whose instructors design their own partnerships and assignments, this contribution examines TAPP projects in light of language policies from a dual bottom-up/top-down perspective. Thus, considering the importance of language policies of several European countries involved in TAPP (Belgium, France, Italy, Spain), this paper analyses how TAPP teaching-learning practices align with such policies in terms of multilingualism and interculturality. Attention is paid to students' roles – subject-matter experts, linguists/translators, project managers, usability experts – and their native languages. Emphasis is placed on how students relate to English from their various perspectives as native speakers, second-language speakers, language experts or language learners. Lessons derived from the analysis of such practices can inform policy makers as they make provisions for Internationalisation at Home, mainly in Europe, while also introducing comparisons between European and US perspectives.